Techniques for Implementing the Iktisyaf Method in Teaching the Yellow Book at Pesantren Puncak Darussalam, East Java, Indonesia - M. Husnaini; Ahmad Syauqi Fuady; Yusuf (Jurnal Pendidikan Agama Islam, 2023)
Purpose – This study aims to examine the iktisyaf technique applied by teachers to accelerate the Yellow Book understanding by the santri at Pesantren Puncak Darussalam Islamic in East Java, Indonesia. Design/methods/approach – This study used qualitative methods with an exploratory approach to obtain an in-depth understanding. Data were obtained from teachers who have applied the iktisyaf method in the learning process. This study used a combination of interviews and observations as research instruments, followed by manually analyzed data and information. Findings – There are five techniques used by pesantren teachers to teach the Yellow Book through the iktisyaf method: question and answer, tutorials or public lectures, direct instruction, repetition, and memorization. The pesantren teachers have used those techniques to apply the iktisyaf method in teaching and learning the Yellow Book. These techniques are often integrated. Research Implications/Limitations – This study has shown the iktisyaf techniques in teaching the Yellow Book, allowing future researchers to examine the strengths and weaknesses of each technique to conduct additional research on more effective and innovative iktisyaf techniques for teaching the Yellow Book in the classroom.